THE IMPACT OF BILINGUALISM ON HUMAN COGNITION - Xolboyeva Moxinur Nursaid qizi (Bright Mind Publishing, 2026)
This piece explores the cognitive impacts of being bilingual, emphasizing executive functions, attention, memory, and problem-solving skills. Utilizing a qualitative examination of current academic literature, the research references contributions from notable scholars including Bialystok, Costa, Kroll, and Luk. The results show that bilingual people demonstrate greater cognitive flexibility, inhibitory control, and attention management than monolinguals. Age of acquisition, language skill, and frequency of language use are recognized as significant factors impacting cognitive results. The study emphasizes that bilingualism represents not just a linguistic event but also a cognitive aspect, carrying important consequences for education, cognitive growth, and ongoing learning.
Keywords: Bilingualism, human cognition, attention, memory, problem – solving, cognitive flexibility, executive functions.